Lower Incidence of M2/ANXA5 Carriage in Recurrent Pregnancy Loss Patients With Elevated Lipoprotein(a) Levels. (October 2014) - Rogenhofer, Nina; Engels, Laura; Bogdanova, Nadja; Tüttelmann, Frank; Thaler, Christian J; Markoff, Arseni
This study compared the incidence of M2/ANXA5 haplotype carriage, a documented repeated miscarriage risk factor, in patient groups with normal and elevated lipoprotein(a) (Lp(a)) levels. A total of 138 women with ≥2 consecutive, idiopathic recurrent miscarriages, categorized in patients with elevated (≥30 mg/dL, n = 44) and normal Lp(a) level (<30 mg/dL, n = 94) were recruited at the recurrent pregnancy loss (RPL) clinic of Munich Großhadern University Hospital. A total of 500 fertile women served as controls. All patients were genotyped for ANXA5 promoter haplotypes, genetic frequencies were compared, and odds ratios (ORs) and relative risks of M2 carriers were calculated. Women with M2 haplotype had an almost 2 times higher relative risk of RPL (OR 2.6, 95% confidence interval 1.5-4.6, P = .001) than fertile controls. Furthermore, risk rises to 2.47 in patients having normal Lp(a) levels (OR 3.2, 95% confidence interval 1.7-5.9, P = .001), whereas women with high Lp(a) levels exhibit notably lower apparent RPL risk of 1.39 (OR 1.4, 95% confidence interval 0.5-4.1, P = .659).